Effectivity of Restrain Management Training on Nurses at RSKD Dadi, South Sulawesi Province - A. Nur Anna. AS; St Suarniati; Abdul Halim; Wahyunita Nur; Khairunnisah Khairunnisah (Jurnal Kesehatan Manarang, 2023)
Background: Schizophrenia is a mental disorder with a very high prevalence in Indonesia, which is around 7 million per 1000 population (Riskedas, 2018). Schizophrenia can cause sufferers to behave aggressively, which can cause injury to the patient himself or other people, including nurses. If the client's aggressive behavior increases, the actions that can be applied are crisis management and restraint strategies. Objective: to determine the effect of restraint management on the knowledge, skills, and attitudes of nurses at RSKD DADI, South Sulawesi Province. Method: The type of research used is a quasi-experiment. The sample was divided into two groups: intervention and control groups. This research was conducted in November 2022. The population for this study were nurses at RSKD DADI South Sulawesi Province; the sample was determined by consecutive sampling, namely 20 people in the intervention group and 20 people in the control group, so the total sample was 40 people. Results: There is a significant difference in the mean knowledge of nurses regarding restraint management between the control group (M=7.75, SD=1.585) and the intervention group (M=10.05, SD=3.170) with a t-test value of 3.359, and a p-value of <0.003. There is a significant difference in the mean skills of nurses between the control group (M=29.85, SD=3.92) and the intervention group (M=34.25, SD=1.743) with a t-test value of 5.646 and a p-value of <0.000. There is a significant difference in the attitudes of nurses between the control group (M=21.35, SD=4.107) and the intervention group (M=24.70, SD=5.611) with a t-test value of 2.258, and a p-value of <0.036. Conclusion: The research findings showed a significant increase in the mean scores of knowledge, attitude, and skills after participating in the restraint training.